Intraspecific facilitation of the recruitment of a burrowing mangrove crab species along an environmental gradient - Anders Jensen Schmidt; Karen Diele (Ocean and Coastal Research)
The exploited mangrove crab Ucides cordatus, an important ecosystem engineer in South American mangroves, has a biphasic lifecycle with pelagic larvae developing offshore. Megalopae return to the mangrove forest to settle, i.e., metamorphose into benthic juveniles but its environmental drivers remain poorly understood. We postulate that conspecific crabs facilitate recruitment. In the field, we investigated whether the number of recruits is higher near conspecific burrows than in areas without conspecific bioturbation. Recruit sampling was conducted monthly from April 2008 to May 2009 along an environmental gradient. First, U. cordatus recruits of that year emerged from March to July. Intraspecific facilitation was indicated by significantly higher recruit numbers in bioturbated than in non-bioturbated substrates. Recruits were most abundant in zones with intermediate conditions of inundation, leaf litter standing stock, sediment consistency, luminosity, temperature, salinity, and pH. Avoidance of more inundated zones likely reduces predation by fishes and of less inundated zones helps individuals escape more stressful, drier environmental conditions. The observed habitat-specific recruitment pattern must be considered when designing field assessments of the population structure of U. cordatus (which should include sampling recruits) and enhancing stocks by releasing laboratory-cultivated larvae and first juveniles into the wild.